OPTIMASI STRATEGI UNTUK MENINGKATKAN MOTIVASI DAN PENGETAHUAN GURU DENGAN PENDEKATAN SIMULASI BERBASIS AGEN - Dhanan Sarwo Utomo (EDUCARE, 2008)
School is an organization which has certain goals that want to be achieved. Appropriate strategy analysis is essential in order to achieve these goals successfully. Interaction exists among students, teachers, parents and school managers within school organization. Each elements of this interaction have different goals and strategy to achieve their individual goals. The result of this interaction will affect the overall outcome of school’s strategy. Using hypothetical data we construct an agent based computer simulation to analyze interaction within school organization. Based on our simulation we analyze the effect of teacher’s performance standard and the interval of teacher evaluation toward teacher’s motivation and knowledge. As a result, we purpose several scenarios that can optimize teacher’s motivation and knowledge.Key Words: strategy analysis, school strategy, agent based simulation.